Analysis Of Economic Growth and Income Inequality Among Province in Indonesia 2018 – 2022 - Agustin, Rahayu Anzelina; Rachmad Kresna Sakti (Journal of Development Economic and Social Studies, 2025)
The success of economic development can be characterized by an increase in economic growth and equitable development. However, in reality, the increase in economic growth is not necessarily followed by equity. This is evidenced by the persistence of inequality in several aspects related to development between regions in Indonesia. One of them is income inequality by calculating the Williamson Index which shows an upward trend from 2018 - 2022. Therefore, it is necessary to conduct a more in-depth research related to the causality between economic growth and income inequality, as well as the factors that influence these two aspects in the period 2018 - 2022. This study applies a simultaneous equation model through the use of the Inderect Least square (ILS) method. The results of the analysis show that (1) income inequality and IP-ICT have a significant negative effect on economic growth. (2) TPAK and PMTB significantly affect economic growth in a positive direction. (3) Income inequality is significantly positively affected by economic growth. (4) Total population, TPAK, and IP-ICT have a significant negative effect on income inequality. (5) There is a unidirectional causality from economic growth to income inequality.   Abstrak Keberhasilan pembangunan ekonomi dapat ditandai oleh kenaikan pertumbuhan ekonomi dan pemerataan pembangunan. Namun, kenyataannya kenaikan pertumbuhan ekonomi belum tentu diikuti oleh pemerataan. Hal ini terbukti dengan masih adanya ketimpangan dalam beberapa aspek terkait dengan pembangunan antar wilayah di Indonesia. Salah satunya adalah ketimpangan pendapatan melalui perhitungan Indeks Williamson yang menunjukkan kecenderungan kenaikan dari tahun 2018 – 2022. Oleh sebab itu, perlu dilakukan penelitian secara lebih mendalam terkait dengan kausalitas antara pertumbuhan ekonomi dan ketimpangan pendapatan, serta faktor-faktor yang mempengaruhi kedua aspek tresebut pada periode 2018 – 2022. Penelitian ini menerapkan model persamaan simultan melalui penggunaan metode Inderect Least Square (ILS). Hasil analisis yang telah dilakukan,  menunjukkan bahwa (1) ketimpangan pendapatan dan IP-TIK berpengaruh negatif signifikan terhadap pertumbuhan ekonomi. (2) TPAK dan PMTB mempengaruhi pertumbuhan ekonomi ke arah positif secara signifikan. (3) Ketimpangan pendapatan secara signifikan positif dipengaruhi oleh pertumbuhan ekonomi. (4) Jumlah penduduk, TPAK, dan IP-TIK berpengaruh negatif signifikan terhadap ketimpangan pendapatan. (5) Terdapat hubungan satu arah (unidirectional causality) dari pertumbuhan ekonomi terhadap ketimpangan pendapatan.